CLASSROOM ACTION RESEARCH (CAR): Preparing Future Teachers in Action - Dwi Septian (Universitas Lancang Kuning, 2015)
Preparing English language teachers should involve more than providing techniques, recipes, and tips.Classroom Action Research (CAR) is useful not only in preparing future teachers but for all teachers to continue togrow and develop as reflective practitioners. This article presents an overview of the components of classroomaction research (selecting an issue, refining the research question, and undertaking data collection, analyzingmultiple forms of data, developing and implementing new instructional strategies, and making the research findingspublic). An example of an action research project on giving feedback on student writing is used to illuminate thesesteps. For teachers to develop their practice after finishing formal preparation, they must be able to question andimprove their teaching practices in response to changing conditions and experiences (Richards & Lockhart, 1994).Not only can action research be integrated into teacher preparation programs so future teachers can try out teachingmethods and approaches, but it is also a useful way for current teachers to investigate issues in their teaching